Retiring the Flip Phones: Exploring Social Media Use for Managing Public Health Incidents. (December 2019) - Khan, Yasmin; Tracey, Shannon; O'Sullivan, Tracey; Gournis, Effie; Johnson, Ian
ABSTRACT: Objective: Communication is essential during public health emergencies and incidents. This research aimed to understand current uses and challenges for public health agencies using social media during these incidents. Methods: An exploratory, qualitative study was conducted using the structured interview matrix facilitation technique. Focus groups were held with professionals from local public health agencies across Ontario, Canada. Representation from different geographic regions was sought to capture differences in participant experience. An inductive approach to content analysis was used to identify emergent themes. Results: A diverse group of public health professionals (n = 36) participated. Six themes were identified. Social media is identified as a communication tool used to expand reach of messages, to engage in dialogue with the public, and to inform the scope of potential incidents. Barriers to its use include hesitancy to adapt, lack of trust and credibility, and organizational structure and capacity constraints. Key strategies proposed to promote social media use and address barriers resulted from participant discussions and are presented. Conclusion: Social media use is highly variable across public health agencies in Ontario. This study identifies and provides strategies to address barriers and practice gaps related to public health agencies' use of social media during emergencies.